2007
DOI: 10.1007/s00436-007-0619-3
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Calf Coccidiosis (Eimeria spp.) in Poland

Abstract: The field survey has been performed to study the epidemiology of calf coccidiosis in Poland. It was found that the Eimeria spp. coccidia occurred on 93.0 % of the investigated farms. But the highly pathogenic species (E. bovis and E. zuernii) were found on 88.4 % of the investigated farms. Those were also found more frequently in bigger farms (92.3 %) compared to smaller ones (85.1 %). However, the intensity of E. bovis as well as E. zuernii infection remained, in most cases, low -75.4 and 79.8 % or moderate -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 1 publication
1
16
3
3
Order By: Relevance
“…Research performed in other countries has revealed prevalence rates of Eimeria spp. varying from 17.9% to 93% in Poland (Pilarczyk et al 2000;Klockiewicz et al 2007;Pilarczyk et al 2009), 33% in Hungary (Farkas et al 2007), 22.6% and 33.3% in Brazil (Almeida et al 2011;Poscoti-Bruhn et al 2011), 35% to 47.1% in China (Yu et al 2011;Dong et al 2012), 50% in Pakistan (Nisar-Khan et al 2013), 22.7% and 68% in Ethiopia (Abebe et al 2008;Dawid et al 2012), 20%, 68% and 75% in Turkey (Arslan and Tuzer 1998;Cicek et al 2007;Nalbantoglu et al 2008), 29%, 50% and 52% in South Africa (Matjila and Penzhorn 2002), and 35% in Tanzania (Chibunda et al 1997). The rate was reported to be 21.3% and 18% to 50% in the Kurdistan and East-Azerbaijan provinces of Iran (Yakhchali and Gholami 2008;Yakhchali and Zarei 2008;Davoudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research performed in other countries has revealed prevalence rates of Eimeria spp. varying from 17.9% to 93% in Poland (Pilarczyk et al 2000;Klockiewicz et al 2007;Pilarczyk et al 2009), 33% in Hungary (Farkas et al 2007), 22.6% and 33.3% in Brazil (Almeida et al 2011;Poscoti-Bruhn et al 2011), 35% to 47.1% in China (Yu et al 2011;Dong et al 2012), 50% in Pakistan (Nisar-Khan et al 2013), 22.7% and 68% in Ethiopia (Abebe et al 2008;Dawid et al 2012), 20%, 68% and 75% in Turkey (Arslan and Tuzer 1998;Cicek et al 2007;Nalbantoglu et al 2008), 29%, 50% and 52% in South Africa (Matjila and Penzhorn 2002), and 35% in Tanzania (Chibunda et al 1997). The rate was reported to be 21.3% and 18% to 50% in the Kurdistan and East-Azerbaijan provinces of Iran (Yakhchali and Gholami 2008;Yakhchali and Zarei 2008;Davoudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Em 86 fazendas polonesas a prevalência nos animais investigados foi de 80,1% em bezerros de 3 a 9 meses, 18,2% naqueles de um a três meses e 1,7% entre os com 9 e 18 meses (KLOCKIEWICZ et al, 2007 GRISI, 1984;REBOUÇAS et al, 1994;ALMEIDA et al, 2011;BRUHN et al, 2012) Em estudo realizado por Lima et al (1997) em Minas Gerais com bezerros do nascimento aos 27 meses de vida, os animais começaram a se infectar por helmintos gastrintestinais antes dos 2 meses de idade, e apresentaram período crítico dessas infecções até os 18 meses. Neste estudo, a maior ocorrência de eliminação de ovos se deu nos animais com mais de 45 dias de vida, tendo idade média de 64,9 dias.…”
Section: -------Intervalo De Confiança _______ Risco Relativo Ajustadounclassified
“…However, the intensity of E. bovis as well as E. zuernii infection remained, in most cases, low -75.4 and 79.8 %, or moderate -21.3 and 18.5 %, respectively. The intensity of the infections was, respectively, 3.1 and 1.9 times higher in big farms (Klockiewicz et al, 2007). Becker and Frye, 1929 (fi gs 5, 6) Oocysts are ellipsoidal, 18-26 x 3-18 µm in size.…”
Section: Family Eimeriidae Minchin 1903mentioning
confidence: 99%
“…subspherica, E. bovis, E. zuernii, E. bukidnonensis, E. brasiliensis, E. cylindrica, E. ellipsoidalis, E. canadensis, E. wyomingensis, and E. alabamensis (Mironenko, 2001;Yatusevich, 2006). Th e study of the epidemiology of coccidiosis in Poland (Klockiewicz et al, 2007) showed the occurrence of disease with diff erent association caused by one or a several 12 Eimeria species in infected calves.…”
Section: Remarksmentioning
confidence: 99%